Optical image encryption scheme with extended visual cryptography and non-mechanical ptychographic encoding. (1st February 2022) - Yu, Han; Li, Yong; Zhang, Junhao; Yang, Dongyu; Ruan, Tianhao; Wang, Huaying; Shi, Yishi
Abstract: Non-mechanical ptychographic encoding (NPE) transforms the secret information into series of diffractive patterns through a spatial light modulator (SLM), saving the need to fabricate the secret objects. Conventionally, the shares in extended visual cryptography (EVC) are printed on transparent sheets or fabricated with diffractive optical elements and metasurface, but these methods are expensive and disposable. To solve these problems, we proposed an optical image encryption scheme that combines EVC and NPE. In the encryption process, the secret image is decomposed into multiple shares that are digitally loaded on the SLM, and the ciphertexts are generated according to the ptychographic encoding scheme. The decryption is performed by superimposing the shares reconstructed from the ciphertexts. We present optical experiments to demonstrate the feasibility and effectiveness of the proposed method.